Satellite telemetry reveals habitat selection decisions by black oystercatchers across seasonal, diel, and tidal cycles. Issue 4 (7th April 2023) - Ware, Lena; Hipfner, John Mark; Green, David J.
Abstract: Habitat use of indicator species is used to prioritize management activities. However, habitat use can vary temporally in response to changes in predation risk and foraging rewards. We deployed satellite tags on 20 black oystercatchers ( Haematopus bachmani ) in four regions of British Columbia, Canada, to examine habitat use and selection decisions across seasonal, diel and tidal cycles. We characterized the shoreline in each region and used GLMMs to investigate how habitat characteristics influenced shoreline use by tracked birds. For individuals, we estimated home range size and the frequency key features of the shoreline were re‐visited. Black oystercatchers generally made greater‐than‐expected use of rocky islets and shoreline with freshwater outflows, less tree cover and greater intertidal area. However, while black oystercatchers preferred islets and shoreline with less tree cover at most/all time periods, they only exhibited preferences for greater intertidal area during low tides, and preferences for shoreline with freshwater outflows during the nonbreeding season, day, and high tides. Individual home ranges, on average, contained 46 km of shoreline (range: 12–156 km) and individuals used 10.4 km (range: 6.7–13.9 km). Individuals made greater use of larger islets with less tree cover that were closer to outflows, and greater use of outflows associated with larger streams, greater intertidal areas and gravel substrates. Black oystercatchers' habitat preferences likely reduce predation risk (rocky islets and shoreline with less tree cover) and increase foraging rewards (shoreline with freshwater outflows, greater intertidal area, and gravel substrates). However, habitat preferences appear sensitive to constraints on movement in the breeding season and changes in foraging rewards across the diel and tidal cycle, highlighting the importance of examining habitat use at multiple temporal scales. Black oystercatchers are considered indicators of rocky intertidal health; therefore, critical habitat is expected to be important for a suite of wildlife dependent on safe and productive coastline. Abstract : We examined how habitat use of black oystercatchers varied in response to changes in predation risk and foraging rewards by tracking birds across seasonal, diel, and tidal cycles. Black oystercatchers used safe rocky islets and shoreline with less tree cover at most times and more dangerous shoreline with greater intertidal area and freshwater outflows during low and high tides, respectively, when foraging rewards at these sites are likely higher. Identifying critical habitat that is expected to be indicative of important habitat for coastal wildlife requires studying habitat use at different times.